Dades per a una anàlisi del teatre a Catalunya. 1939-1993 - Gallén, Enric (Caplletra. Revista Internacional de Filologia, 2015)
Throughout this work the author carries out a study of the trajectory of Catalan drama from the end of the Civil War to present times. The analysis of problems relating to censorship, the lack of infrastructure, the dialectics of commercial versus alternative theatre, the successive appearances of new theatrical writers and groups, the dominating theatrical norms and the important support provided in recent years by public institutions presents a perfect scan of the issues Catalan drama has faced during the mentioned period.